MENILAI DAMPAK SOSIAL-EKONOMI DARI PERJUDIAN ONLINE MELALUI LENSA EKONOMI SYARIAH: ANALISIS MENDALAM - Judijanto, Loso; Indarsih, Fajar; Natsir, Imron; Al-Amin, Al-Amin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research analyzes the socio-economic impact of online gambling using sharia economic principles. This study was conducted through an in-depth literature review. Various relevant sources and publications were examined. This includes journals, books, and articles from experts in Islamic economics. The results of this study reveal that online gambling is in contradiction with the basic values of sharia economics which emphasize justice and mutual prosperity. Its presence triggers economic imbalance and causes widespread social losses. In accordance with sharia economics, economic transactions should have added value and real benefits for the entire community. Based on literature analysis, this research offers insight into the need for sharia-oriented responses and policies. The aim is to overcome the challenges brought by online gambling. Emphasis is placed on understanding and implementing the values of sharia justice. This is not only important for strengthening the economic structure but also for increasing social harmony. This study proves the urgency of action based on sharia economic principles. This is to answer and overcome the negative effects of online gambling.